Penerapan Sistem Among di Sd Al-Qur’an Darul Ishlah Tahun Ajaran 2020/2021 - Apri Eka Budiyono (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study is to determine the application of the Among System in the learning process at SD Al-Qur'an Darul Ishlah. This research uses qualitative research. The subjects of this study were the principal, teachers, students. Data collection techniques used observation, interviews, documentary studies, audio and visual materials. The data analysis technique used includes area analysis, taxonomic analysis, and component analysis in the overall process. The results showed that the application of the among system in SD Al-Qur'an Darul Ishlah has been going well. The Among Ki Hadjar Dewantara system is an appropriate method for education because it is a teaching and education method based on love, hone and nurture. The application of the among system at SD Al-Qur'an Darul Ishlah is also applied outside the classroom, this can be seen from the full of kinship between the principal and the teacher, the principal and the employee, the principal and the students, the employee and the teacher, the employee and the student, the teacher. with students, students with students, while paying attention to courtesy. The Among system is an education system that emphasizes the spirit of kinship and is based on the nature of nature and independence. The elements of the among system are the tri centers of education, namely education in the family, education in schools and education in the community. The motto of the system among them is Ing ngarso sung tulodho, Ing madyo mangun karso karso and Tut wuri handayani